SEQUENCE OF IMPLEMENTATION OF INTRAPRENEURSHIP AT ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The sequence of implementation of intraprenership at mechanical engineering enterprises, which includes the analysis of the potential and feasibility of introducing intraprenership at the enterprise; formation of organizational culture of intraprenership; development of organizational principles and legal support for the implementation of intraprenership; creation of support structures for intraprenership at the enterprise; expert evaluation, approval of the project, development of a business plan of selected ideas; creation of an intraprenership unit; creation of a system of incentives for the subjects of intraprenership, provision of resources, support, monitoring of the activities of the intraprenership unit; implementation of the project; analyzing the results of the activities of the intraprenership unit is elaborated in the paper. The system of support for the implementation of intraprenership at the enterprise, structured into administrative, cultural, incentive, financial and economic and resource elements is suggested by the author. One of the main tasks of intraprenership is to find the most promising ways of attracting and using resources. In this regard, we distinguish a separate element of the support system, which is primarily associated with the provision of timely supply, regulation and control for the rational use of resources. The scheme of resource support of the intraprenership process at the enterprise is presented.  It is important to use existing enterprise resources that are not involved in the main production of the project for introducing intraprenership and selecting promising ideas. It is natural that managers are primarily interested in innovative ideas of this type, especially when initiative workers propose to use the waste of basic production.It is proposed to classify the resources of the enterprise according to the form of ownership into internal and external. The internal resources, in addition to the resources of the enterprise, include the resources of an intraprener, primarily intellectual, it is stated that the need to attract external sources of resources implies the implementation of the project through exopreneurship.In the context of this study, it is necessary to note the special role of workforce, because any employee who performs a passive role in the implementation of a specific intraprenership project is perceived as a potential introducer by the managers of the enterprise.
Keywords: innovative activity, intrapreneurship, support of intrapreneurship, enterprise of intrapreneurship type, resource support of intrapreneurship.